Analisis Penerimaan Teknologi Menggunakan Theory of Interpersonal Behavior Pada Pengguna Aplikasi E-Commerce - Damula, Ariel Putra Wijaya; Tambotoh, Johan J.C (STMIK Banjarbaru, 2024)
E-commerce refers to buying, selling, or transaction activities conducted through electronic media. Various e-commerce applications have emerged to facilitate people in purchasing desired goods. However, the rapid development of e-commerce poses challenges in the acceptance and use of e-commerce applications. This research aims to identify various aspects that influence individuals in using e-commerce applications using the Theory of Interpersonal Behavior, which includes variables such as attitude, social factors, emotional, habit, intention, facilitating condition, and behavior. The method used in this research is quantitative, with a total of 100 respondents. The research results show that the factors influencing intention and behavior in using E-commerce applications consist of Social Factors and Facilitating Conditions. This means that the use of E-commerce applications is heavily influenced by external factors such as environment and adequate facilities.Keywords: Theory of Interpersonal Behavior; Attitude; Social Factors; Emotional; HabitÂ AbstrakE-commerce merupakan kegiatan jual beli atau transaksi yang dilakukan menggunakan sarana media electronic, berbagai aplikasi e-commerce hadir untuk memudahkan manusia dalam membeli barang yang diinginkan. Namun perkembangan e-commerce yang semakin cepat menimbulkan tantangan dalam penerimaan dan penggunaan aplikasi e-commerce. Penelitian ini bertujuan untuk mengetahui berbagai aspek yang mempengaruhi seseorang dalam penggunaan aplikasi e-commerce menggunakan Theory of Interpersonal Behavior yang memiliki variabel attitude, social factors, emotional, habit, intention, facilitating condition dan behavior. Metode yang digunakan dalam penelitian ini adalah kuantitatif, dengan jumlah 100 responden. Hasil penelitian diperoleh bahwa faktor yang mempengaruhi niat dan perilaku dalam penggunaan aplikasi E-commerce terdiri dari Social Factors, dan Facilitating Condition. Artinya penggunaan aplikasi E-commerce sangat dipengaruhi oleh faktor eksternal seperti lingkungan dan fasilitas yang memadai.Â